Primerjava dveh presejalnih metod za odkrivanje influence A, influnce B in RSV - Prosenc, Katarina (Zdravstveno varstvo, 2004)
Acute respiratory tract infections (ARI) are the leading cause of increased morbidity and mortality in winter months. Because of nonspecific clinical symptoms of influenza, laboratory confirmation is essential for surveying influenza spread in the community. Rapid tests, such as enzyme linked immunoassay (ELISA) and multiplex reverse transcription-polymerase chain reaction (RT-PCR), were introduced to replace the time-consuming isolation of influenza and RSV viruses. Multiplex RT-PCR allows for detection of three different antigens during a single test. The test was adapted to enable reverse transcription and DNA replication to be processed in the same reactionmix. Throat and nasal swabs were obtained from out-patients and in-patients with ARI. ELISA identified influenza A in 2.5%, influenza B in 6.3% and RSV in 2% of the 605 clinical samples tested. Detection rates achieved by RT-PCR were 3.6%, 18.6 % and 3%, respectively. For isolation in cell culture all ELISA and/or RT-PCR-positive samples were used. Influenza A virus was recovered from two, influenza B from 33 and RSV from five samples. RT-PCR was found to be a more sensitive test than ELISA. It improved the rateof virus isolation from RT-PCR-positive samples, which is of utmost importance for typification and sub-typification of influenza viruses. Higher sensitivity of RT-PCR was established in all age groups. RT-PCR yielded betterdetection results than ELISA, especially in the age group 5 years and over. Despite its higher cost and greater expertise required, RT-PCR offers a significant advantage over ELISA, and is superior to it in influenza screeningand RSV detection.
Keywords: diagnostika; ELISA; influenca